«Your book... is the best gift for me»-V.M. Bekhterev (Dedicated to the 159th birth anniversary of V.M. Bekhterev) - M. A. Akimenko; T. . Asser (Обозрение психиатрии и медицинской психологии имени В.М. Бехтерева, 2018)
In December 2015, the scientific community commemorated the 140th birth anniversary of L.M. Puusepp, and in February 2016 we will mark the 159th birth anniversary of V.M.Bekhterev. Both scientists were among the pioneers of the new specialty - surgical neuropathology, which was focused mainly on brain tumor surgery. The article presents the previously unknown correspondence between the two scientists.